ALLERGIC DISEASES IN CHILDREN (World Bulletin of Public Health, 2024)
Allergic diseases are a global public health problem. Allergic rhinitis is the most common in both paediatric and adult populations. According to WHO data, more than 40% of the population in developed countries have signs of allergic readiness. Currently, the incidence of allergic rhinitis in the general population is 10-20% and these figures tend to further increase this disease. This disease limits the life activity of children, reduces their social and physical activity, as well as their quality of life and general well-being in general [6]. According to the results of epidemiological studies, allergic rhinitis affects about 20% of the population of all age groups. According to various data, 54-75% of patients with allergic diseases have a hereditary predisposition. The relationship between the course of AR and the functional state of the autonomic nervous system (ANS), peculiarities of vegetative changes in different forms and severity of the disease course, their dynamics under the influence of various methods of treatment, targeted correction, morphological changes in the nasal cavity tissues taking into account the initial vegetative tone (IVT) of the organism are not properly reflected